Supplementation level increasing dry matter intake of beef cattle grazing low herbage height - Barbero, Rondineli Pavezzi; Malheiros, Euclides Braga [UNESP]; Aguilar, Natalia María; Romanzini, Elieder Prates [UNESP]; Ferrari, Adriana Cristina [UNESP]; Nave, Renata La Guardia; Mullinks, John Travis; Reis, Ricardo Andrade [UNESP] (Taylor & Francis, 2020)
To evaluate the foraging behaviour of yearling bulls grazing on Marandu grass, we conducted two experiments. In the first experiment (Exp. 1), three grazing heights of 15, 25, and 35 cm were evaluated, with bulls receiving 0.3% of body weight (BW) of supplement (161 g kg–1 crude protein (CP) and 20.1 MJ kg–1 gross energy (GE)); in the second experiment (Exp. 2), supplementation levels were decreased as grazing height increased: (1) low height (15 cm) and high supplementation (0.6% BW: 142 g kg–1 CP and 18.9 MJ kg–1 GE (LH-HS)); (2) moderate height (25 cm) and moderate supplementation (0.3% BW: 161 g kg–1 CP and 20.1 MJ kg–1 GE (MH-MS)) or (3) high height (35 cm) without supplementation (HH-WS). Ingestive behaviour was evaluated by direct visual observations, and intake using markers. It was used 9 paddocks each experiment. The experimental design was completely randomized, analysing effects by polynomial orthogonal contrasts (Exp. 1) and Tukey test (Exp. 2). In Exp. 1, a linear decreasing response to daily grazing time (P < 0.01) was observed, whereas a linear increasing response to herbage intake (P < 0.01) was observed with increased grazing height. In Exp. 2, LH-HS bulls had lower herbage intake (P < 0.01) than their counterparts. Bulls from both experiments showed increased grazing activity after 12 PM (P < 0.05). The herbage intake substitution effect of supplements can be explored as a production strategy, as the adjustment of supplementation levels can promote high dry matter intake as well as performance in beef cattle, in conditions of low grazing height or low forage allowance, even with a high stocking rate.
Keywords: Bite rate; herbage intake; supplements; tropical grasslands